(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to prepare exercises to develop the accuracy of scoring from jumping to develop the scoring accuracy of a sample of Al-Sulaikh Club players in basketball. Two players for each group. The experiment was conducted in the hall of Al-Sulaikh Sports Club with basketball on 15/1/2015 to 1/3/2015. The experimental approach was used due to its suitability to the nature of the problem. After completing the experiment, (spss) was used to extract the special statistics. In the research, the results of the research showed the development of the experimental group over the control group in the post-tests and in favor of the experimental group.